Como as intervenções parentais atuam no desenvolvimento infantil na primeira infância: revisão de literatura - Karine Saraiva da Silva; Virna da Costa e Silva; Roseny Marinho Mesquita Pereira; Renata de B. Bruno Ximenes (Residência Pediátrica)
OBJECTIVE: To describe and evaluate the main models of parental intervention. METHODOLOGY: A search was carried out for randomized clinical trials in two electronic databases: PUBMED and Embase, during the period from 2018 to 2022. Articles with a primary outcome on child development in children during early childhood with typical development were included, including 19 articles. RESULTS: As a result, we obtained 3 main intervention models: feedback model of the child-caregiver interaction, model with face-to-face delivery of instructions and model of remote delivery by application, with language and behavior domains being the most evaluated, mainly in pre-school children. school. The strategy that was most effective in child development was the model with greater interaction between caregiver-child and with the training team, with a minimum intervention time of one year for a sustained effect on the evaluated domains. CONCLUSION: The heterogeneity of the models makes more detailed evaluations difficult, requiring new evaluations with more homogeneous parameters in order to allow more consistent results. There is no conflict of interest.